2000
DOI: 10.1016/s0092-8674(00)80678-9
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog-Regulated Processing of Gli3 Produces an Anterior/Posterior Repressor Gradient in the Developing Vertebrate Limb

Abstract: Ci/Gli zinc finger proteins mediate the transcriptional effects of Hedgehog protein signals. In Drosophila, Ci action as transcriptional repressor or activator is contingent upon Hedgehog-regulated, PKA-dependent proteolytic processing. We demonstrate that PKA-dependent processing of vertebrate Gli3 in developing limb similarly generates a potent repressor in a manner antagonized by apparent long-range signaling from posteriorly localized Sonic hedgehog protein. The resulting anterior/posterior Gli3 repressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
994
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 953 publications
(1,033 citation statements)
references
References 54 publications
39
994
0
Order By: Relevance
“…Nevertheless, although a mesenchyme-specific null mutation of Bmpr1a leads to a drastic down-regulation of the two Msx genes (Ovchinnikov et al, 2006), residual expression is still detectable for both Msx1 and Msx2 anteriorly, raising the possibility that, in this region, Msx genes are controlled by other factors such as, for example, Gli3R (Lallemand et al, 2009). Indeed, it has been shown that the Talpid 2 chick mutation, which precludes proper processing of Gli3 into Gli3R (Wang et al, 2000) also abolishes Msx2 expression and leads to nonpolarized Msx1 expression in the mesoderm (Krabbenhoft and Fallon, 1992). Most of the results quoted here, however, suggest that Msx might work as downstream effectors in the BMP pathway for most of the limb mesenchyme, and indeed, the Fgf4 expression domain in the AER extends anteriorly in a similar way in the Msx conditional double mutant and the Bmp4 conditional null mutant (Selever et al, 2004;this work).…”
Section: Bmp Signaling and Control Of Bmp4 Expressionmentioning
confidence: 99%
“…Nevertheless, although a mesenchyme-specific null mutation of Bmpr1a leads to a drastic down-regulation of the two Msx genes (Ovchinnikov et al, 2006), residual expression is still detectable for both Msx1 and Msx2 anteriorly, raising the possibility that, in this region, Msx genes are controlled by other factors such as, for example, Gli3R (Lallemand et al, 2009). Indeed, it has been shown that the Talpid 2 chick mutation, which precludes proper processing of Gli3 into Gli3R (Wang et al, 2000) also abolishes Msx2 expression and leads to nonpolarized Msx1 expression in the mesoderm (Krabbenhoft and Fallon, 1992). Most of the results quoted here, however, suggest that Msx might work as downstream effectors in the BMP pathway for most of the limb mesenchyme, and indeed, the Fgf4 expression domain in the AER extends anteriorly in a similar way in the Msx conditional double mutant and the Bmp4 conditional null mutant (Selever et al, 2004;this work).…”
Section: Bmp Signaling and Control Of Bmp4 Expressionmentioning
confidence: 99%
“…The decreased expression of two Hh target genes in Fuz mutants in the face of the normal Shh expression suggests an abnormality in the Hh signal transduction. The transcriptional repressor activity of Gli3 is required to control the number of digits formed in mammalian limbs (Wang et al, 2000). Therefore, we investigated whether the Gli3 repressor production, that is, the proteolytic processing of Gli3, is abnormal in Fuz mutants.…”
Section: Abnormal Hh Signaling In Fuz Mutant Embryosmentioning
confidence: 99%
“…Both Gli2 and Gli3 can function either as transcriptional activators or transcriptional repressors when the activator domain is removed by proteolytic processing. However, in vivo studies suggest that Gli3 is much more efficiently processed than Gli2, making it the major transcriptional repressor of Hh target genes (Wang et al, 2000;Pan et al, 2006). Gli1 is generally believed to exist only as a transcriptional activator, although a recent study appears to challenge this belief (Dai et al, 1999;Stecca and Ruiz i Altaba, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…5 Although both GLI2 and GLI3 have transcriptional activation and repression properties, GLI1 is a strong positive regulator of SHH transcriptional targets and is itself a transcriptional target of SHH. [6][7][8][9] Chemotherapy resistance remains a significant impediment to the successful treatment of patients with diffuse large B-cell lymphoma. The multidrug resistance phenotype is often associated with increased expression of ATP-binding cassette (ABC) transporters that mediate energy-dependent transport of substrate drugs out of the cell against a concentration gradient.…”
mentioning
confidence: 99%